2012
DOI: 10.1111/ene.12038
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of ophthalmic artery flow as a predictor of intracranial hemodynamic compromise: implication for prognosis of severe carotid stenosis

Abstract: ROAF may result from intracranial hemodynamic compromise. Patients with unilateral high-grade cervical carotid stenosis/occlusion in combination with intracranial stenosis appear to be a significant risk factor for poor functional outcome and increased incidence of ROAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 26 publications
5
46
0
Order By: Relevance
“…Moreover, it was demonstrated that ROAF was highly associated to the combination of stenosis of the cervical and intracranial segments and less well correlated to high-grade cervical carotid stenosis/occlusion alone. Additionally, similarly to the presence of intracranial stenosis and previous stroke, ROAF was shown to be associated with a poorer functional outcome [9].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, it was demonstrated that ROAF was highly associated to the combination of stenosis of the cervical and intracranial segments and less well correlated to high-grade cervical carotid stenosis/occlusion alone. Additionally, similarly to the presence of intracranial stenosis and previous stroke, ROAF was shown to be associated with a poorer functional outcome [9].…”
Section: Introductionmentioning
confidence: 93%
“…The ROAF in the setting of significant ICA (≥70%) is not infrequent, with some reports estimating an incidence of approximately 25% [8,9]. However, its role in cerebral collateralization is somewhat controversial [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Because it has multifactorial causes, 2 identification of its underlying pathogenesis and risk factors is essential. 3,4 As a part of the phase I oxidizing enzyme aldehyde dehydrogenase (ALDH) superfamily, ALDH2 is responsible for both ethanol metabolism and biogenic and xenogenic aldehyde detoxification. 5,6 ALDH2 activity deficiency has been reported to increase the risk of cardiovascular disorders.…”
mentioning
confidence: 99%
“…The estimated prevalence of middle cerebral artery stenosis among asymptomatic Asian patients ranges from 7.2% to 29.6%, while Asian patients with ischemic stroke have a higher ICS incidence of 33% to 84% 4, 19. Further, concurrent atherosclerosis of intracranial and extracranial vessels is not uncommon in Asian populations13, 20, 21, 22; in fact, ≈20% to 50% of patients with ECS are reported to also have ICS 22, 23, 24. In this study, we found that 51.4% of patients with ECS had concurrent ICS.…”
Section: Discussionmentioning
confidence: 99%